Purity and almost strict purity of Anderson $t$-modules - Alexis, Lucas (Comptes Rendus. Mathématique)
We study the relations between the notion of purity of a $t$-module introduced by Anderson and that of almost strict purity for a $t$-module introduced by Namoijam and Papanikolas (concept already mentioned by G. Anderson and D. Goss).